The atomization current and droplet size of ethanol in two different small-scale electro-spraying systems - Gan, Yunhua; Zhang, Xia; Li, Haige; Tong, Yang; Shi, Yanling; Yan, Yuying (Elsevier, 2017)
An experimental study on electro-spraying from small-scale combustors is carried out using liquid ethanol as fuel. Two systems of electro-spraying are employed in the present study; one is a nozzle system (without a ring electrode) and the other is a nozzle-ring system (with a ring electrode). The photos of electro-spraying at the cone-jet mode are taken by a digital camera. The voltage drop across the resistance in the loop is measured by a data acquisition instrument, and the atomization current is calculated according to Ohm's Law. The size and velocity of electro-spraying droplets are measured by a Phase Doppler Anemometer. A non-dimensional analysis on atomization current is completed to explain the electro-spraying phenomena of liquid at the stable cone-jet mode. The results show that, the lower atomization current and droplet velocity corresponds to smaller size of droplet. Based on the results of non-dimensional analysis, it is found that the dimensionless atomization current in both the nozzle system and nozzle-ring system obeys the scaling law as square root of the dimensionless flow rate. The charge density is of a −1.5 power dependence on droplet diameter. Both of the nozzle and the nozzle-ring systems show a good agreement with Rayleigh instability.